Respon Masyarakat Terhadap Program Tempat Olah Sampah Setempat (TOSS) Di Desa Gunaksa, Kabupaten Klungkung - Komang Ema Marsitadewi; I Wayan Sudemen; Lilik Antarini (Journal of Contemporary Public Administration, 2021)
Based on data from the Bali Provincial Environmental Service, the amount of waste generated or in other words the volume of waste or the weight of waste produced in Bali continues to increase every year. Klungkung occupies the second position with waste piles reaching 2,893 cubic meters per day. The waste capacity overload that occurred in various areas in Bali including Klungkung Regency was used as an opportunity for the Klungkung Regent to produce an innovation in waste management in Klungkung Regency. This innovation is known as the Local Waste Processing Site (TOSS) Program. This innovation, which was initiated by the Regent of Klungkung, is the only local government waste management innovation in Bali Province. The method used in this study is a quantitative method. Data obtained from primary data and secondary data. Primary data was obtained by distributing questionnaires by 98 respondents and field interviews with informants. While secondary data is obtained from reports, scientific articles or similar research related to the Local Waste Processing Site (TOSS) Program. Based on the results of the analysis of the Community Response Variables to the Local Waste Processing Place (Toss) Program in Gunaksa Village, the community desire to act/actively participate is very low.